(untitled) (Schermi. Storie e culture del cinema e dei media in Italia, 2024)
Closely associated with cinema since its beginnings, Venice represents a case of great interest regard- ing film exhibition history. Its historical, geographical, and demographic peculiarities have shaped the distribution of cinemas and the moviegoing practices. This contribution investigates the history of Venetian movie theatres in the central decades of the 20th century, putting them in relation to the urban and social developments of the city, divided in three main macrozones (historic centre, main- land and lagoon). Other factors such as population movements, industrial and tourist developments, the presence of the annual film festival are also examined, as they have influenced the relationship of the city and its inhabitants with movie theatres and with the practice of moviegoing. From this analysis, Venice emerges as a polycentric metropolis, characterized by dynamics of film exhibition and consumption that differ from area to area.